Modulation of Intestinal Microbiota in Solea senegalensis Fed Low Dietary Level of Ulva ohnoi - Tapia-Paniagua, Silvana T.; Fumanal, Milena; Anguís, Victoria; Fernández-Díaz, Catalina; Alarcón, F. Javier; Moriñigo, Miguel A.; Balebona, M. Carmen (Frontiers in Microbiology, 2019)
Gastrointestinal (GI) microbiota has a relevant role in animal nutrition, modulation of the immune system and protection against pathogen invasion. Interest in algae as source of nutrients and functional ingredients for aquafeeds is increasing in order to substitute conventional feedstuffs by more sustainable resources. The diet is an important factor in the modulation of the microbiota composition, and functional ingredients have been proposed to shape the microbiota and contribute benefits to the host. However, fish microbiome research is still limited compared to other hosts. Solea senegalensis is a flat fish with high potential for aquaculture in South Europe. In this study, a characterization of the microbiome of S. senegalensis (GI) tract and the effects of feeding Ulva ohnoi supplemented diet has been carried out. Differences in the composition of the microbiota of anterior and posterior sections of S. senegalensis GI tract have been observed, Pseudomonas being more abundant in the anterior sections and Mycoplasmataceae the dominant taxa in the posterior GI tract sections. In addition, modulation of the GI microbiota of juvenile Senegalese sole fed for 45 days a diet containing low percentage of U. ohnoi has been observed in the present study. Microbiota of the anterior regions of the intestinal tract was mainly modulated, with higher abundance of Vibrio spp. in the GI tract of fish fed dietary U. ohnoi.